Evaluation of phytochemical constituents and antimicrobial activity of leaves and stem bark extracts of sarcocephalus latifolius (2018)
Sarcocephalus latifolius is reported to have a wide range of medicinal properties and it is commonly used in the treatment of malaria, hypertension, diarrhea, dysentery and dental problems. Considering its characteristics, it is important to identify the phytochemical constituents and further evaluate the antimicrobial activity. Thus, this study was designed to identify the phytochemical constituents and to evaluate the antimicrobial activity of the leaf and stem bark extracts of Sarcocephalus latifolius on bacteria strains isolated from dental samples. The phytochemical compounds in leaf and stem bark extracts of Sarcocephalus latifolius were analyzed using GC-QPMS. The mixture of bioactive compounds present in leaf and stem extracts of Sarcocephalus latifolius were tested against Gram-positive and Gram-negative bacteria for inhibition of growth using agar-cup-diffusion method. Results emerging from this study show that a total of 19 compounds and 25 compounds were identified from the leaf and stem bark extracts respectively. Decanoic acid, decanoic acid, benzene carboxylic acid and terpenes; phytol and farnesyl acetatewere identified to be the main constituents. Furthermore, the extracts at concentrations of 25-50 mg/ml inhibited the growth of bacteria isolates in a manner that is comparable to the standard antibiotic (p<0.05). The significant zones of inhibition of bacterial growth by leaf and stem extracts of Sarcocephalus latifolius validates the use of extracts of Sarcocephalus latifolius in traditional medicine and as a promising source of antimicrobial agents.